Analisis Gaya Komunikasi Akun Instagram Rekan Santri Garis Lucu Sebagai Media Dakwah Kultural Di Media Sosial - Bagus Sujatmiko; Muhammad Amrillah; M. Choirul Wachid (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2026)
The rapid development of communication technology has transformed Islamic da'wah from conventional face-to-face interactions into digital communication practices. Instagram has become one of the most effective platforms for delivering religious messages, especially among young audiences. This study aims to analyze the communication style used by the Instagram account Rekan Santri Garis Lucu, identify its communication strategies in constructing da'wah messages, and examine the representation of cultural and Islamic values reflected through its content. This research employed a library research approach using primary data from Instagram content and secondary data from relevant literature. Data collection techniques included documentation, literature review, and interviews, while data analysis utilized Robert Entman’s framing analysis. The findings reveal that the account adopts a dialogical and participatory communication style characterized by humor, everyday language, and narrative-reflective messages. Its communication strategy is audience-centered, focusing on issues closely related to young people's lives and supported by systematic content planning. Furthermore, the account represents Islamic values through cultural symbols, tolerance, togetherness, self-reflection, and learning spirit, creating an image of Islam that is friendly, inclusive, and relevant to contemporary digital culture.